2011
DOI: 10.1590/s1516-89132011000500001
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical composition of seven species of cyanobacteria isolated from different aquatic habitats of Western Ghats, Southern India

Abstract: The aim of this work was to study the biochemical constituents of seven species of cyanobacteria namely,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 41 publications
(38 reference statements)
3
17
0
1
Order By: Relevance
“…Nonetheless, there are some useful generalized distinctions that are found with regard to the cellular content of cyanobacteria compared to algae, and plants. Under ideal growth conditions, cyanobacteria tend to be composed of relatively low carbohydrate (10–30%), intermediate lipid (5–10%) and high protein levels (40–79%), in comparison to algae (5–60% carbohydrate, 1–40% lipid, 20–50% protein) and plants (70–80% carbohydrate, 1–15% lipid, 1–10% protein) (Rajeshwari and Rajashekhar 2011; Becker 1994). With regard to carbohydrates, the dominant carbon sinks for cyanobacteria are glycogen and their exopolysaccharide layers.…”
Section: Cyanobacterial Carbohydrate Content and Natural Sugarsmentioning
confidence: 99%
“…Nonetheless, there are some useful generalized distinctions that are found with regard to the cellular content of cyanobacteria compared to algae, and plants. Under ideal growth conditions, cyanobacteria tend to be composed of relatively low carbohydrate (10–30%), intermediate lipid (5–10%) and high protein levels (40–79%), in comparison to algae (5–60% carbohydrate, 1–40% lipid, 20–50% protein) and plants (70–80% carbohydrate, 1–15% lipid, 1–10% protein) (Rajeshwari and Rajashekhar 2011; Becker 1994). With regard to carbohydrates, the dominant carbon sinks for cyanobacteria are glycogen and their exopolysaccharide layers.…”
Section: Cyanobacterial Carbohydrate Content and Natural Sugarsmentioning
confidence: 99%
“…Some studies reported Spirullina and Nostoc commune contains highest amount of protein and fibre that make it an important component of human diet. Scytonema and Tolypothrix, although its lower protein content in comparison to L. majuscula, Spirullina and Nostoc commune isolated from stream system but it presented almost equal values of protein in ranges than those found for freshwater algae and marine red algae (Ciferri and Tiboni, 1985;Rajeshwari and Rajashekhar, 2011;Gressler et al, 2011), which have been used in a variety of foods throughout the world (Gantar and Svircev, 2008). Thus, Tolypothrix and Scytonema followed by other species examined could be more studied to become an option of fibres source to healthy food industry after proper scientific investigation.…”
Section: Resultsmentioning
confidence: 90%
“…Фенольные соединения представляют собой класс антиоксидантов, которые действуют как терминаторы свободных радикалов. Эти соединения были тщательно изучены в отношении их антиоксидантных свойств не только у фруктов и овощей, но и у цианобактерий (Rajeshwari, Rajashekhar, 2011). Известно, что фенольные соединения водорослей являются потенциальными антиоксидантами для борьбы со свободными радикалами, вредными для организма человека.…”
Section: результатыunclassified